2007
DOI: 10.1002/pssa.200776315
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate effects on the thermoluminescence kinetics properties of MWCVD diamond films

Abstract: Dose rate effects are important in thermoluminescent (TL) dosimeter applications because a certain absorbed dose given at different dose rates may result in a different TL yield. The present work reports about the dose rate effects on TL glow curves and kinetics properties of microwave plasma assisted chemical vapor deposition (MWCVD) diamond films grown on (100) silicon. The diamond films were exposed to γ radiation at 20.67, 43.4 and 81.11 Gy min–1 dose rates in the range of 0.05–10 kGy. The films showed a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Dose rate effects at higher radiation dose rates were recently reported for undoped CVD diamond films 7, 8, 22. Dose rate of 2.4–81.1 Gy/min accounted for a TL increase of 1–2 and 150% for low (20 Gy) and high (90 Gy) total dose, respectively.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Dose rate effects at higher radiation dose rates were recently reported for undoped CVD diamond films 7, 8, 22. Dose rate of 2.4–81.1 Gy/min accounted for a TL increase of 1–2 and 150% for low (20 Gy) and high (90 Gy) total dose, respectively.…”
Section: Resultsmentioning
confidence: 74%
“…Diamond is considered a tissue equivalent material because its atomic number ( Z = 6) is close to the effective atomic number of tissue ( Z eff = 7.4 for muscle) 1, and its non‐toxicity make it an appropriate material for detectors and dosimeters in bio‐medical applications 2–4. However, it has been observed that the thermoluminescence (TL) response may depend on the irradiation dose rate used to excite the TL in some chemically vapor deposition (CVD) diamond 5–8. It may cause that same irradiation dose, at different dose rates, may result in different integrated TL response, which makes a real dose assessment difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 43 ] MWCVD diamond films exhibit a TL repeatability of 3% deviation during the read‐out of successive cycles. [ 44 ] . HPHT diamond presents a nonreproducible TL glow curve shape due to the presence of nitrogen defects.…”
Section: Resultsmentioning
confidence: 99%
“…Several TL characteristics like sensitivity, dose dependence, fading, and the linearity dose response of diamond have been investigated . However, one of the most important variables in dosimetry is the dose rate effect that may change the TL response at same doses . The trapping and recombination processes can influence dose rate effects during ionization by irradiation.…”
Section: Introductionmentioning
confidence: 99%